A Study on the Possibility of Extraction, Identification and Removal of Metallic Ions and Resins in Bleached Bagass Pulp by ECF Stages - Ramin Veisi (Regional Information Center for Science and Technology (RICeST), 2015)
This study and it aim was accomplished on extraction, identification and removal of metallic ions and resins in bleached Bagass pulp by ECF stages. For this purpose, the samples were randomly selected from soda unbleached pulp of Pars mill. The first, pulp flour provided and measured ash and extractive percent by the TAPPI standards. Then the mineral compounds dissolved in 65% nitric acid and the mineral compounds of pulps identificated by Atomic adsorption method. The results of this study showed that the most of Pb, Cu, Zn ions were in H2O2 bleached pulp, the most of Ni ion in OD(Ep)P stage and the most of Fe ion in unbleached soda pulp. The results showed that OD(Ep)D stage decrease Fe ion and EH stage decrease Ni, Cu and Zn ions in pulps. The results of GC-MS diagram showed that 35 compounds were identified in unbleached soda pulp after cooking, that 1,2-Benzendicarboxylic acid, Hexadecanoic acid, Hexadecan, Octadecan, p-Xylene, 4-Hydroxy-4-Methyl-2-Pantanone,Ethylbenzen and Dodecan were important chemical components in samples. In generally, 17,12 and 14 compounds were identified in EH, OD(Ep)P and OD(Ep)D bleaching stages, respectively, so that, 1,2-Benzendicarboxylic acid and p-Xylene were 2 common and important chemical components in all samples and Octadecan and 9-Dodecanoic acid remove as two components from pulps after bleaching, too. The results showed that EH, OD(Ep)P and OD(Ep)D bleaching stages were very important in bleaching, removal of chemical components and brightness stability of soda pulps.